Genetic Association Of Arginase 1 Gene Polymorphism (Rs60389358, And Rs2781666) With Valvular Heart Diseases Of Type 2 Diabetic (The Review of Diabetic Studies, 2025)
Background: Most prevalent metabolic disease (Type 2 diabetes; T2DM) can accelerate the development of valvular heart diseases (VHD) and that Arginase 1(Arg1) is an important enzyme involved in many metabolic pathways. Objective. The association of Arg1 genetic polymorphisms as well as its functional effects on VHD with and without T2DM were estimated. Methods: samples of blood were collected from T2DM, heart valves with T2DM (VHDM) and without (VHD) patients, as well healthy controls. In this work, two Arg1 SNPs (rs60389358 and rs2781666) and their sequencing were examined to assess the allele frequencies in addition to the genotype for the chosen collections. Results: Data showed that the genotype as well as the allele of both SNPs were non- significant (P >0.05) for T2DM and VHD group compared to controls. However, the C and T allele frequencies for the rs60389358 SNP in VHDM patients were significantly different; OR and 95% Cl (0.34, (0.12 -0.92) and 2.96(1.09 -8.01), P < 0.05 respectively) compared to controls. Moreover, the rs2781666 SNP in VHDM patients was significant with controls comparison (in genotype frequencies in GG and TT genotype; OR,,and 95% Cl (0.14 ,(0.03-0.65) ,and 7.36,(1.34- 40.55),P < 0.05 ,respectively ). As well, the G and T allele; OR,and 95%CI (0.21, (0.08-0.53) , and (4.90 ,(1.90-12.67),P < 0.001 ,respectively in comparison with controls. Conclusions: Genetic variations of the Arg1 gene may play a role as a potential predisposing factor for T2DM disease complications and its progression to VHD susceptibility risk in the Iraqi population.